Halal Label and Product Quality: Case Study Wardah Cosmetic Product Purchase Decision - Lily Ulfia; Mamluatul Maghfiroh; Rachma Indrarini (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2021)
The development of the Indonesian cosmetic industry is relatively rapid because cosmetic products have become a primary need in Indonesia which the population is predominantly Muslim. This development caused competitive competition between cosmetics brands in Indonesia. Because of this competition, Wardah cosmetics is considering the halal label in its products and the quality of the products to increase consumer purchasing decisions. This research uses quantitative, associative methods to investigate the relationship between halal brands and product quality with the purchasing decision of Wardah cosmetics, especially in Surabaya. The number of samples used is 100 Muslim respondents who used Wardah cosmetics products in Surabaya. The data analysis technique used is multiple correlation coefficient analysis using SPSS version 25. The study results showed that halal labeling and product quality simultaneously had a significant and robust relationship with the purchasing decision of Wardah cosmetic products. While partially, the halal labels and product quality had a moderate and meaningful relationship with the purchase decision of Wardah cosmetics products.